Aliphatic-aromatic polyester as well as preparation method and application thereof

By esterification in three stages and controlling the amount of titanate catalyst, the problem of high dimer and by-product content in polyester materials is solved, and the effect of narrow molecular weight distribution and high product quality is achieved.

CN119684579APending Publication Date: 2025-03-25SINOPEC YIZHENG CHEM FIBER +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311232880.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing polyester materials have high dimers, oligomers and by-product content, which affects processing application and product quality.

Method used

By esterifying the aromatic dibasic acid monomer and the aliphatic dibasic alcohol monomer in three stages, and adding a catalyst and a pH adjusting agent during the esterification process, the amount of the titanate catalyst is controlled to be less than or equal to 0.00033 mol.

Benefits of technology

The production of dimers, trimers, pentamers and by-products in polyester is significantly reduced, and the utilization rate of reaction monomers is improved. The obtained polyester has a narrow molecular weight distribution, which is suitable for subsequent processing applications and improves product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004464537470000081
    Figure BDA0004464537470000081
  • Figure BDA0004464537470000091
    Figure BDA0004464537470000091
Patent Text Reader

Abstract

The invention relates to a polyester material, and discloses aliphatic-aromatic polyester as well as a preparation method and application thereof. In the polyester, the content of Ti is less than or equal to 70ppm, the content of dimer is less than or equal to 0.44 wt%, the content of trimer is less than or equal to 0.27 wt%, and the content of pentamer is less than or equal to 0.081 wt%. The preparation method comprises the following steps: (1) under an esterification reaction condition I, mixing an aromatic dibasic acid monomer, an aliphatic dibasic alcohol monomer, a catalyst and a pH regulator, and carrying out a first-stage reaction to obtain a mixture I; (2) carrying out a second-stage reaction under an esterification reaction condition II to obtain a mixture II; (3) carrying out a third-stage reaction under an esterification reaction condition III to obtain a prepolymer; and (4) carrying out fourth-stage reaction under the polycondensation reaction condition. The content of oligomers in the polyester is lower, byproducts in the reaction process are fewer, and the phenomena of more broken ends, higher fiber irregularity and the like in the spinning process can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polyester materials, in particular to an aliphatic-aromatic polyester and a preparation method and application thereof. Background Art

[0002] Polybutylene terephthalate (PBT) is an important engineering plastic with the advantages of good flowability, high toughness, wear resistance, high elongation, chemical corrosion resistance and good formability. At present, there are two synthetic preparation processes for PBT, one is the direct esterification reaction between PTA and butanediol (BD), and the other is the transesterification reaction between dimethyl terephthalate (DMT) and BD. During the direct esterification reaction, a part of BD will undergo a side reaction to generate tetrahydrofuran (THF). Since the activation energy of the main reaction to generate PBT is similar to that of the side reaction to generate THF, the side reaction of THF generation and the esterification reaction of PBT are accompanied by each other. The two are parallel competing reactions, making it difficult to inhibit the side reaction of THF generation.

[0003] The existing technology mainly suppresses the generation of THF in the esterification process by using a composite catalyst or optimizing the production process. Patent CN108892770B discloses a method for suppressing the side reaction of THF in the polymerization process, by adding a guide, a titanium silicon cobalt composite catalyst dispersion and a pH regulator in the esterification stage, and controlling the molar ratio of terephthalic acid to 1,4-butanediol to 1:1.05-1.10, so that the THF content in the polymer is ≤10wt%; although this method can reduce the amount of tetrahydrofuran generated, it requires the preparation of a guide, the procedure is cumbersome and increases the processing cost, and the cobalt in the composite catalyst is a heavy metal, and the processing and use will cause pollution to the environment; and the output of THF and oligomers in the preparation process is still high.

[0004] Patent CN102924698B discloses a method for preparing a titanium catalyst for the synthesis of polybutylene terephthalate and its application. The titanium catalyst used in the invention is a stable, uniform, hydrolysis-resistant liquid composition. The titanium catalyst uses a titanium compound as the main catalyst and introduces phosphorus and one of the acetates of Na, Li, Mg, and Zn. The catalyst can prepare PBT products with excellent performance, but the preparation process of the catalyst is relatively complicated and difficult to apply in industrial production; and the output of THF and oligomers in the preparation process is still high.

[0005] The existing technology mostly uses compound catalysts to reduce the amount of THF generated. The preparation of compound catalysts is generally cumbersome and there are difficulties in the process of industrial application. If the compound catalyst contains inorganic or weakly acidic substances, it will be difficult to obtain PBT products with high intrinsic viscosity, and the content of by-products such as oligomers is relatively high, which affects the processing application and product quality of PBT products. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem that there are many dimers in the polyester in the prior art, which affects its processing application and product quality, and to provide an aliphatic-aromatic polyester and a preparation method and application thereof.

[0007] The inventors of the present invention have found in the course of research that by esterifying aromatic dibasic acid monomers and diol monomers in three stages, adding a catalyst and a pH regulator during the esterification process, and controlling the addition amount of the titanate catalyst to be less than or equal to 0.00033 mol, the production of dimers, trimers, pentamers, diol dehydration products, other by-products and the content of Ti in the polyester can be greatly reduced, and the content of impurities such as dimers, trimers, other by-products and titanium-containing compounds in the prepared polyester can be effectively reduced, thereby obtaining polyester with a narrow molecular weight distribution, facilitating subsequent processing and application, effectively reducing the occurrence of more broken ends and higher fiber unevenness during the spinning process, and ensuring the quality of the prepared product.

[0008] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides an aliphatic-aromatic polyester, in which the Ti content is less than or equal to 70 ppm, the dimer content is less than or equal to 0.44 wt%, the trimer content is less than or equal to 0.27 wt%, and the pentamer content is less than or equal to 0.081 wt%.

[0009] The second aspect of the present invention provides a method for preparing an aliphatic-aromatic polyester, comprising the following steps:

[0010] (1) under esterification reaction condition I, an aromatic dibasic acid monomer, an aliphatic diol monomer, a catalyst and a pH adjuster are mixed and then subjected to a first stage reaction to obtain a mixture I;

[0011] The catalyst contains titanate, and the amount of the titanate added is less than or equal to 0.00033 mol relative to 1 mol of the aromatic dibasic acid monomer;

[0012] (2) subjecting the mixture I to a second-stage reaction under esterification reaction conditions II to obtain a mixture II;

[0013] (3) subjecting the mixture II to a third-stage reaction under esterification reaction conditions III to obtain a prepolymer;

[0014] (4) Under polycondensation conditions, subjecting the prepolymer to a fourth stage reaction.

[0015] The third aspect of the present invention provides the use of the aforementioned polyester or the polyester prepared by the aforementioned preparation method in spinning.

[0016] The polyester provided by the present invention, in the preparation process, the aromatic dibasic acid monomer and the aliphatic diol monomer are esterified in three stages, and a catalyst and a pH regulator are added during the esterification process, and the addition amount of the titanate catalyst is controlled to be less than or equal to 0.00033 mol, which can greatly reduce the generation of oligomers and diol dehydration products, effectively improve the utilization rate of the reaction monomers, and effectively reduce the content of oligomers and the content of titanium-containing impurities in the prepared polyester, thereby making the molecular weight distribution of the prepared polyester narrower, facilitating subsequent processing and application, effectively reducing the occurrence of more broken ends and higher fiber unevenness during the spinning process, and ensuring the quality of the prepared product. It can also alleviate the situation of rapid equipment scaling caused by titanium hydrolysis, and extend the cleaning cycle of the polyester production device.

[0017] In addition, the use of titanate and basic aluminum acetate as catalysts can not only promote the esterification reaction and polycondensation reaction, but also help to obtain products with high characteristic viscosity and low impurity content, which is convenient for subsequent application in spinning. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] As described above, the first aspect of the present invention provides an aliphatic-aromatic polyester, in which the Ti content is less than or equal to 70 ppm, the dimer content is less than or equal to 0.44 wt%, the trimer content is less than or equal to 0.27 wt%, and the pentamer content is less than or equal to 0.081 wt%.

[0020] According to the present invention, dimer refers to a dimer of an esterification product of a monomer, trimer refers to a trimer of an esterification product of a monomer, and pentamer refers to a pentamer of an esterification product of a monomer. Specifically, when the polyester is PBT (polybutylene terephthalate), the dimer is a dibutyl terephthalate (BHBT) dimer, the trimer is a dibutyl terephthalate trimer, and the pentamer is a dibutyl terephthalate pentamer.

[0021] The polyester has a low content of impurities such as dimer, trimer, pentamer, and titanium, which is convenient for subsequent processing and application, effectively reduces the occurrence of more broken ends and higher fiber unevenness during the spinning process, and can ensure the quality of the prepared product. In addition, the titanium content is controlled to be less than or equal to 70 ppm, which can effectively reduce the generation of oligomers in the polyester during the preparation process.

[0022] According to the present invention, the content of Ti in the polyester is 30-70 ppm, that is, based on the weight of all solid substances in the polyester, the content of Ti is 30-70 ppm. Preferably, the content of Ti in the polyester is 40-70 ppm.

[0023] Preferably, in the polyester, the heptamer content is less than or equal to 0.045 wt %. The impurity content in the polyester is lower, which further facilitates subsequent processing and application and increases its application range.

[0024] Preferably, in the polyester, the Ti content is less than or equal to 45 ppm, the dimer content is less than or equal to 0.41 wt %, the trimer content is less than or equal to 0.268 wt %, and the pentamer content is less than or equal to 0.079 wt %, which further facilitates its subsequent application in spinning.

[0025] According to the present invention, the dimer, trimer, pentamer and heptamer contents can be measured according to the method in GB / T 36214.2-2018 / ISO 16014-2:2012.

[0026] Preferably, the polydispersity coefficient of the polyester is less than or equal to 1.73, and the intrinsic viscosity of the polyester is 1.1-1.2 dL / g.

[0027] According to the present invention, the polydispersity index PDI is tested according to the test standard "GB / T 36214.2-2018 / ISO 16014-2:2012"; the intrinsic viscosity is tested and characterized according to 5.1 of "GB / T14190-2017 Test Method for Fiber-Grade Polyester Chips".

[0028] The polyester provided above has a narrow molecular weight distribution, fewer impurities, and a higher intrinsic viscosity, which can facilitate subsequent processing. The obtained product has a higher quality and has a better application in spinning.

[0029] Preferably, the polyester further contains metal element A and metal element B; the metal element A is selected from at least one of the elements of group IA, specifically any one of lithium, sodium and potassium, and the metal element B is selected from at least one of the elements of group IIIA, specifically aluminum and / or gallium. Adding the above metal element A and metal element B during the preparation process can effectively reduce the yield of by-products (the content of impurities) during the preparation process, thereby effectively reducing the polydispersity index PDI of the polyester. Considering that the yield of by-products of polyester can be further reduced, preferably, the content of the metal element A is 15-55ppm, and the content of the metal element B is 0-35ppm. Further preferably, the molar ratio of the metal element A to Ti is controlled at (2.45-2.65):1, under which condition, the generation of by-products of polyester can be significantly reduced. More preferably, the weight ratio of the metal element A, the metal element B and the Ti is (1.1-1.3):(0.6-0.8):1. From the perspective of being able to reduce the impurity content of polyester while saving costs, preferably, the metal element A is sodium and / or potassium, and the metal element B is aluminum.

[0030] According to the present invention, the content of metal elements in the polyester can be measured by elemental analysis. Specifically, the sample is processed by microwave digestion using inductively coupled plasma emission spectroscopy, and the processed sample is tested by inductively coupled plasma emission spectroscopy to obtain the metal content.

[0031] As mentioned above, the second aspect of the present invention provides a method for preparing an aliphatic-aromatic polyester, comprising the following steps:

[0032] (1) under esterification reaction condition I, an aromatic dibasic acid monomer, an aliphatic diol monomer, a catalyst and a pH adjuster are mixed and then subjected to a first stage reaction to obtain a mixture I;

[0033] The catalyst contains titanate, and the amount of the titanate added is less than or equal to 0.00033 mol relative to 1 mol of the aromatic dibasic acid monomer;

[0034] (2) subjecting the mixture I to a second-stage reaction under esterification reaction conditions II to obtain a mixture II;

[0035] (3) subjecting the mixture II to a third-stage reaction under esterification reaction conditions III to obtain a prepolymer;

[0036] (4) Under polycondensation conditions, subjecting the prepolymer to a fourth stage reaction.

[0037] According to the present invention, the end condition of the third stage reaction can be determined by the test personnel according to the actual situation, preferably, it can be determined according to the amount of water in the product. In a specific embodiment of the present invention, the end condition of the first stage reaction is: when the amount of water collected reaches the theoretical value, the esterification reaction ends, which can be specifically 0.5-1.5h. The end condition of the fourth stage reaction can also be determined by the test personnel according to the actual situation, preferably, it can be determined according to the viscosity of the reaction system or according to whether the stirring current reaches the rated value. In a specific embodiment of the present invention, the end condition of the fourth stage reaction is: the stirring current reaches the rated value. Wherein, the aromatic dibasic acid monomer can be terephthalic acid and / or isophthalic acid.

[0038] During the reaction, part of the diol monomer will undergo intramolecular dehydration to obtain a dehydrated product during the esterification reaction. This reaction is carried out simultaneously with the esterification reaction and is inevitable.

[0039] According to the present invention, the titanate is 0.00015-0.00033 mol relative to 1 mol of the aromatic dibasic acid monomer.

[0040] The preparation method provided by the present invention esterifies aromatic dibasic acid monomers and aliphatic diol monomers in three stages, adds a pH regulator during the esterification process, and controls the addition amount of titanate to be less than or equal to 0.00033 mol, which can greatly reduce the generation of oligomers and diol dehydration products, effectively improve the utilization rate of reaction monomers, and effectively reduce the content of by-products in the prepared polyester, thereby making the molecular weight distribution of the prepared polyester narrower, facilitating subsequent processing and application, and ensuring the quality of the prepared product. It can also alleviate the situation of rapid equipment scaling caused by titanium hydrolysis, and extend the cleaning cycle of the generating device.

[0041] The addition of pH regulator can adjust the pH value of the reaction system, reduce the acidity of the reaction system, and reduce the side reactions such as dehydration of diol molecules caused by acid catalysis. It also has a catalytic effect on esterification and polycondensation reactions. When used together with basic aluminum acetate, it can not only reduce the amount of catalyst tetrabutyl titanate, but also promote the growth of polyester molecular chains, thereby obtaining polyester with a higher molecular weight.

[0042] According to the present invention, the temperature of the esterification reaction condition I is lower than the temperature of the esterification reaction condition II, and the temperature of the esterification reaction condition II is lower than the temperature of the esterification reaction condition III. Preferably, the esterification reaction condition I at least includes: a temperature of 150-170°C, specifically 150°C, 155°C, 160°C, 165°C, 170°C, or any value between these values, and a time of 1-2h, specifically 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, or any value between these values. Under the above conditions, the generation of by-products during the reaction can be further reduced, thereby effectively reducing the content of by-products (impurities) in the obtained polyester. From the viewpoint of being able to further reduce the generation of by-products during the reaction, it is further preferred that the esterification reaction conditions II at least include: a temperature of 170-190°C, specifically 170°C, 175°C, 180°C, 185°C, 190°C, or any value between these values, and a time of 1-2h, specifically 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, or any value between these values; the esterification reaction conditions III at least include: a temperature of 190-220°C, specifically 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, or any value between these values.

[0043] Preferably, in step (1), the molar ratio of the pH regulator to the titanate, calculated on the basis of metal elements, is (2.45-2.65):1. Under this condition, the generation of polyester by-products can be significantly reduced.

[0044] Preferably, in step (1), the molar ratio of the aromatic dibasic acid monomer, the aliphatic diol monomer, the catalyst and the pH regulator is 1000:(1200-2010):(0.25-0.5):(50-300). Under the above molar ratio, the generation of by-products during the reaction can be further reduced, thereby effectively reducing the content of by-products in the obtained polyester. Moreover, different molar ratios of alkyd acid will affect the degree of polymerization of the esterification product of dibasic acid and polyol. When the molar ratio of alkyd acid is high, the alcohol is excessively high, and the degree of polymerization of the esterification product is small, while the degree of polymerization of the esterification product is large. Considering that the generation of by-products during the esterification reaction can be further reduced, it is further preferred that the pH regulator is selected from at least one of sodium phosphate, sodium acetate, sodium citrate, potassium phosphate and potassium citrate. It is further preferred to be at least one of sodium phosphate, sodium acetate and sodium citrate, and more preferably sodium phosphate and sodium citrate, and the molar ratio of sodium phosphate and sodium citrate is 1:(0.35-0.5).

[0045] Preferably, the aliphatic diol is a diol as shown in formula (III);

[0046]

[0047] Among them, R 1 , R 2 , R 3 and R 4 Each is independently C1-C6 alkyl or hydrogen, preferably methyl or hydrogen.

[0048] In order to further reduce the generation of by-products during the reaction, preferably, the catalyst also includes basic aluminum acetate. More preferably, the molar ratio of the titanate to the basic aluminum acetate is 1:(1.1-1.4). The titanate can be tetrabutyl titanate and / or tetraethyl titanate.

[0049] Preferably, the polycondensation reaction conditions at least include: a temperature of 250-255° C. and an absolute vacuum degree of less than or equal to 100 Pa. Under the above conditions, the generation of by-products during the reaction can be effectively reduced.

[0050] The third aspect of the present invention provides the use of the polyester provided in the first aspect or the polyester prepared by the preparation method provided in the second aspect in spinning.

[0051] The polyester provided by the present invention has a narrow molecular weight distribution and less impurities, and can effectively reduce the occurrence of more broken ends and higher fiber unevenness during the spinning process, and has good application in spinning.

[0052] According to a particularly preferred embodiment of the present invention, the method for preparing the polyester comprises the following steps:

[0053] (1) mixing an aromatic dibasic acid monomer, a diol monomer represented by formula (III), a catalyst and a pH adjuster, and reacting the mixture at 150-170° C. for 1-2 hours to obtain a mixture I;

[0054]

[0055] Among them, R 1 , R 2 , R 3 and R 4 Each is independently C1-C6 alkyl or hydrogen;

[0056] The molar ratio of the aromatic dibasic acid monomer, the diol monomer, the catalyst and the pH regulator is 1000:(1200-2010):(0.25-0.5):(50-300); the catalyst comprises titanate and basic aluminum acetate, and the addition amount of the titanate is less than or equal to 0.0003 mol relative to 1 mol of the aromatic dibasic acid monomer; the molar ratio of the titanate and the basic aluminum acetate is 1:(1.1-1.4); the pH regulator comprises sodium phosphate and sodium citrate, and the molar ratio of the sodium phosphate and the sodium citrate is 1:(0.35-0.5);

[0057] (2) reacting the mixture I at 170-190° C. for 1-2 hours to obtain a mixture II;

[0058] (3) heating the mixture II at 190-220° C. until the esterification water reaches the theoretical amount, the esterification reaction is completed to obtain a prepolymer;

[0059] (4) reacting the prepolymer at 250-255° C. to obtain the polyester.

[0060] The preparation method provided by the above preferred embodiment can reduce the proportion of impurities generated by dehydration cyclization of diols, the content of oligomers in the prepared product is relatively low, the molecular weight distribution of the product is relatively narrow, the intrinsic viscosity is relatively high, it has better application in spinning and other aspects, and the quality of the prepared product is better.

[0061] The present invention will be described in detail below through examples.

[0062] In the following embodiments, the detection methods of various parameters and performances are as follows:

[0063] (1) The dimer, trimer, pentamer and heptamer contents were measured according to the method in GB / T 36214.2-2018 / ISO 16014-2:2012.

[0064] (2) The tetrahydrofuran content was measured by gas chromatography using an FDI detector and a polar chromatographic column at a detector temperature of 250°C.

[0065] (3) The polydispersity index (PDI) is tested according to the test standard GB / T 36214.2-2018 / ISO 16014-2:2012.

[0066] (4) The intrinsic viscosity was tested and characterized according to 5.1 of GB / T14190-2017 Test method for fiber-grade polyester chips.

[0067] (5) The molecular weight was determined according to the method in GB / T 36214.2-2018 / ISO 16014-2:2012, and the degree of polymerization of BHBT in the esterification reaction was calculated based on the molecular weight.

[0068] In the following examples, all raw materials were of analytical grade.

[0069] Example 1

[0070] 3.77kg terephthalic acid, 2.5kg 1,4-butanedioic acid, catalyst (1.5g tetrabutyl titanate and 0.8g basic aluminum acetate) and pH regulator (0.35g sodium phosphate and 0.1g sodium citrate) were added to a 20L reactor, and esterified at 160±5℃ for 1h to obtain mixture I; mixture I was esterified at 180±5℃ for 1.5h to obtain mixture II; mixture II was reacted at 195±5℃, and when the esterification water output reached the theoretical value, the esterification end point was reached. Then the vacuum system was turned on, the pressure was reduced to below 100Pa, and the temperature in the reactor was raised to 255℃. Under this condition, the reaction was carried out, and the material was discharged when the stirring power reached the rated value to obtain PBT polyester.

[0071] Example 2

[0072] 3.77kg terephthalic acid, 2.453kg 1,4-butanedioic acid, catalyst (1.45g tetrabutyl titanate and 0.9g basic aluminum acetate) and pH regulator (0.2g sodium phosphate and 0.3g sodium acetate) were added to a 20L reactor, and esterified at 155±5℃ for 2h to obtain mixture I; mixture I was esterified at 175±5℃ for 2h to obtain mixture II; mixture II was reacted at 190±5℃, and when the esterification water output reached the theoretical value, the esterification end point was reached. Then the vacuum system was turned on, the pressure was reduced to below 100Pa, and the temperature in the reactor was raised to 250℃. Under this condition, the reaction was carried out, and the material was discharged when the stirring power reached the rated value to obtain PBT polyester.

[0073] Example 3

[0074] 3.77kg terephthalic acid, 3kg 1,4-butanedioic acid, catalyst (1.45g tetrabutyl titanate and 0.8g basic aluminum acetate) and pH regulator (0.35g sodium phosphate and 0.1g sodium citrate) were added to a 20L reactor, and esterified at 165±5℃ for 1.5h to obtain mixture I; mixture I was esterified at 185±5℃ for 1h to obtain mixture II; mixture II was reacted at 225±5℃, and when the esterification water output reached the theoretical value, the esterification end point was reached. Then the vacuum system was turned on, the pressure was reduced to below 100Pa, and the temperature in the reactor was raised to 250℃. Under this condition, the reaction was carried out, and the material was discharged when the stirring power reached the rated value to obtain PBT polyester.

[0075] Example 4

[0076] PBT polyester was prepared according to the method described in Example 1, except that the catalyst was 1.5 g of tetrabutyl titanate and 1 g of basic aluminum acetate.

[0077] Example 5

[0078] PBT polyester was prepared according to the method described in Example 3, except that the catalyst was 1.5 g of tetrabutyl titanate and 0.5 g of basic aluminum acetate.

[0079] Example 6

[0080] PBT polyester was prepared according to the method described in Example 1, except that the catalyst was 2.5 g of tetrabutyl titanate.

[0081] Example 7

[0082] PBT polyester was prepared according to the method described in Example 3, except that the catalyst was 2.4 g of tetrabutyl titanate.

[0083] Example 8

[0084] PBT polyester was prepared according to the method described in Example 2, except that the pH adjuster was 0.45 g sodium phosphate and 0.25 g sodium citrate.

[0085] Example 9

[0086] PBT polyester was prepared according to the method described in Example 4, except that the pH adjuster was 0.45 g sodium phosphate and 0.25 g sodium citrate.

[0087] Example 10

[0088] PBT polyester was prepared according to the method described in Example 1, except that the pH adjuster was 0.45 g sodium phosphate and 0.25 g sodium citrate.

[0089] Embodiment 11

[0090] PBT polyester was prepared according to the method described in Example 1, except that the pH adjuster was 0.4 g sodium phosphate and 0.3 g sodium citrate.

[0091] Example 12

[0092] PBT polyester was prepared according to the method described in Example 3, except that the amount of butanediol added was 4.1 kg, the catalyst was 1.85 g tetrabutyl titanate and 0.3 g basic aluminum acetate, and the pH regulator was 0.55 g sodium acetate.

[0093] Example 13

[0094] PBT was prepared according to the method described in Example 12, except that the catalyst was 2.2 g of tetrabutyl titanate and the pH adjuster was 0.2 g of sodium phosphate.

[0095] Comparative Example 1

[0096] PBT was prepared according to the method described in Example 12, except that the catalyst was 3.92 g of tetrabutyl titanate and the pH adjuster was 0.5 g of sodium acetate.

[0097] Comparative Example 2

[0098] PBT was prepared according to the method described in Example 3, except that the catalyst was 3.92 g of tetrabutyl titanate and there was no pH adjuster.

[0099] Comparative Example 3

[0100] PBT was prepared according to the method described in Example 3, except that the catalyst was 3 g of tetrabutyl titanate and 0.35 g of basic aluminum acetate, and the pH adjuster was 0.4 g of sodium acetate and 0.3 g of sodium citrate.

[0101] Comparative Example 4

[0102] 3.77kg terephthalic acid, 3kg 1,4-butanedioic acid, catalyst (1.45g tetrabutyl titanate and 0.8g basic aluminum acetate) and pH regulator (0.35g sodium phosphate and 0.1g sodium citrate) were added to a 20L reactor, and esterified at 185±5℃ for 1h to obtain mixture I; mixture I was reacted at 225±5℃, and when the esterification water output reached the theoretical value, the esterification end point was reached. Then the vacuum system was turned on, the pressure was reduced to below 100Pa, and the temperature in the reactor was raised to 250℃. Under this condition, the reaction was carried out, and the material was discharged when the stirring power reached the rated value to obtain PBT polyester.

[0103] Test Case

[0104] The physical and chemical parameters of the polyesters prepared in the above examples and comparative examples are shown in Table 1 and Table 2:

[0105] Table 1

[0106]

[0107] From the results in Table 1, it can be seen that by comparing the examples with comparative examples 1-3, it can be seen that when the Ti content in the polyester is controlled to be less than or equal to 70 ppm, the yields of dimer, trimer, pentamer and by-product tetrahydrofuran are significantly reduced. By comparing the examples with comparative example 4, it can be seen that the three-step esterification method can significantly reduce the yields of dimer, trimer, pentamer and by-product tetrahydrofuran.

[0108] Table 2

[0109] Polydispersity index PDI Degree of polymerization of BHBT in esterification reaction <![CDATA[Intrinsic viscosity / dL.g -1 > S1 1.60 6.3 1.189 S2 1.62 6.1 1.120 S3 1.63 5.9 1.198 S4 1.66 5.8 1.199 S5 1.67 5.5 1.121 S6 1.67 5.5 1.188 S7 1.69 5.4 1.186 S8 1.60 6.3 0.199 S9 1.50 6.8 1.200 S10 1.56 6.6 1.200 S11 1.58 6.5 1.195 S12 1.70 5.4 1.194 S13 1.73 5.2 1.190 D1 2.19 2.1 1.178 D2 2.15 2.5 1.181 D3 2.10 2.6 1.192 D4 2.08 2.8 1.198

[0110] From the results in Table 2, it can be seen that by comparing the examples with comparative examples 1-3, it can be seen that after adding the pH regulator and the co-catalyst basic aluminum acetate, while controlling the amount of titanate, the generation of by-products can be reduced, and the molecular weight distribution of the prepared polyester is narrow. By comparing the examples with comparative example 4, it can be seen that the three-step esterification method can significantly reduce the yield of dimers, trimers, pentamers and by-product tetrahydrofuran, thereby reducing the molecular weight distribution of the prepared polyester.

[0111] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An aliphatic-aromatic polyester, characterized in that In the polyester, the content of Ti is less than or equal to 70 ppm, the content of dimer is less than or equal to 0.44 wt %, the content of trimer is less than or equal to 0.27 wt %, and the content of pentamer is less than or equal to 0.081 wt %.

2. The polyester according to claim 1, characterized in that In the polyester, the heptamer content is less than or equal to 0.045 wt%.

3. The polyester according to claim 1 or 2, characterized in that In the polyester, the Ti content is less than or equal to 45 ppm, the dimer content is less than or equal to 0.41 wt %, the trimer content is less than or equal to 0.268 wt %, and the pentamer content is less than or equal to 0.079 wt %.

4. The polyester according to claim 1 or 2, characterized in that The polydispersity coefficient of the polyester is less than or equal to 1.73, and the intrinsic viscosity of the polyester is 1.1-1.2 dL / g.

5. The polyester according to claim 1 or 2, characterized in that The polyester further contains a metal element A and a metal element B; the metal element A is selected from at least one of the elements of group IA, and the metal element B is selected from at least one of the elements of group IIIA; Preferably, the content of the metal element A is 15-55ppm, and the content of the metal element B is 0-35ppm; Preferably, the weight ratio of the metal element A, the metal element B and the Ti is (1.1-1.3):(0.6-0.8):1; Preferably, the metal element A is sodium and / or potassium, and the metal element B is aluminum.

6. A method for preparing an aliphatic-aromatic polyester, characterized in that: The steps include: (1) under esterification reaction condition I, an aromatic dibasic acid monomer, an aliphatic diol monomer, a catalyst and a pH adjuster are mixed and then subjected to a first stage reaction to obtain a mixture I; The catalyst contains titanate, and the amount of the titanate added is less than or equal to 0.00033 mol relative to 1 mol of the aromatic dibasic acid monomer; (2) subjecting the mixture I to a second-stage reaction under esterification reaction conditions II to obtain a mixture II; (3) subjecting the mixture II to a third-stage reaction under esterification reaction conditions III to obtain a prepolymer; (4) Under polycondensation reaction conditions, subjecting the prepolymer to a fourth stage reaction.

7. The preparation method according to claim 6, characterized in that: The temperature of the esterification reaction condition I is lower than the temperature of the esterification reaction condition II, and the temperature of the esterification reaction condition II is lower than the temperature of the esterification reaction condition III; Preferably, the esterification reaction conditions I at least include: temperature of 150-170°C, time of 1-2h; Preferably, the esterification reaction conditions II at least include: temperature of 170-190°C, time of 1-2h; The esterification reaction condition III at least includes: a temperature of 190-220°C.

8. The preparation method according to claim 6 or 7, characterized in that: In step (1), the molar ratio of the aromatic dibasic acid monomer, the aliphatic diol monomer, the catalyst and the pH adjuster is 1000:(1200-2010):(0.25-0.5):(50-300); Preferably, the aliphatic diol is a diol as shown in formula (III); wherein R1, R2, R3 and R4 are each independently C1-C6 alkyl or hydrogen, preferably methyl or hydrogen; Preferably, the pH adjuster is selected from at least one of sodium phosphate, sodium acetate, sodium citrate, potassium phosphate and potassium citrate; Preferably, the catalyst further comprises basic aluminum acetate; Preferably, the molar ratio of the titanate to the basic aluminum acetate is 1:(1.1-1.4).

9. The preparation method according to claim 6 or 7, characterized in that: The polycondensation reaction conditions at least include: a temperature of 250-255° C. and an absolute vacuum degree of less than or equal to 100 Pa.

10. Use of the polyester according to any one of claims 1 to 5 or the polyester prepared according to any one of claims 6 to 9 in spinning.

Citation Information

Patent Citations

  • Preparation method and use of titanium catalyst for synthesis of polybutylene terephthalate

    CN102924698B

  • A method for suppressing tetrahydrofuran side reactions during polymerization

    CN108892770B